Effect of high time under tension strength training on different muscular actions in the performance of runners: A randomized controlled trial - Júlio César de Carvalho Martins; Matheus Santos de Sousa Fernandes; Felipe J. Aidar; Gustavo Ivo de Carvalho e Silva; Eder Magnus Almeida Alves Filho; Fatma Hilal Yagin; Georgian Badicu; Pablo Prieto González; Sameer Badri Al-Mhanna; Mohammed Dauda Goni; Nouf H. Alkhamees; Raphael Fabricio de Souza (PLoS ONE, 2026)
Background Strength training (ST) for runners is typically based on low volumes and high intensities. However, alternative approaches emphasizing higher volume and lower intensity, such as protocols with high time under tension (TUT), remain underexplored in this population. Notably, the effects of high-TUT may vary depending on the predominant type of muscle contraction. Objectives To analyze the impact of strength training with high time under tension on different muscle actions in performance-related variables in runners. Methods Thirty-four physically active young males were randomly divided into three groups: dynamic strength training, isometric strength training, and a control group. Over four weeks, the training groups performed two weekly sessions of bodyweight exercises with equalized time under tension per set (84 s), adjusted according to the type of contraction. The primary outcomes were performance in a 3000-meter time trial, peak torque, countermovement jump, neuromuscular fatigue, internal running load, ground contact time, and vertical oscillation. The data were analyzed using a two-way repeated measures analysis of variance. Results Peak torque increased by 13.3% in the dynamic group and 14.2% in the isometric group, compared with 2.5% in the control, with statistical significance only for the isometric group ( p = 0.034, d = 1.12). Vertical jump height improved by 5.4% in the dynamic group and 4.1% in the isometric group compared with 0.7% in the control ( p = 0.003, d = 1.54 and p = 0.030, d = 1.13, respectively). Conclusion In conclusion, high time under tension strength training, both dynamic and isometric, improved neuromuscular characteristics in runners. However, these adaptations did not translate into significant changes in running performance or running economy over the duration of the intervention. Trial registration This trial was registered in the Brazilian Clinical Trials Registry (ReBEC) with the identifier RBR-686kqdx.